Pengendalian Penyakit Antraknosa (Colletotrichum gloeosporioides Penz)pada Buah Jeruk Siam (Citrus nobilis var. microcarpa) dengan Menggunakan Minyak Atsiri Cengkeh dan Sereh Dapur - KADEK INTAN SURYANINGSIH; I MADE SUDANA; I KETUT SUADA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2015)
ABSTRACT   Anthracnose (Colletotrichum gloeosporioides Penz) DiseaseControlon “Siam”Orange (Citrus nobilis var. microcarpa) by UsingEssential Oilsof CloveandLemongrass The experimental designwas used Factorial Completely Randomized Design, with two  factors: FactorI : CloveEssential Oil with six treatmentstestedconcentration of 0.2%, 0.4%, 0.6%, 0.8%, 1% andwithoutconcentration. FactorII :LemongrassEssential Oil with six treatmentstestedconcentration of 0.2%, 0.4%, 0.6%, 0.8%, 1% andwithoutconcentration. The resultsshowedthat theessential oilof cloveandlemongrassconcentrations below1% cansuppressthe growth offungiC.gloeosporioides. The minimumconcentration ofcloveessential oiltreatmentsthat block100%is0,6% andlemongrassessential oilis0,4%. The effectiveness oflemongrassessential oilis higher thancloveessential oils.   Keywords: Orange,anthracnose, clove, lemongrass